HEDONISME DALAM NOVEL METROPOP CEWEK MATRE KARYA ALBERTHIENE ENDAH - Frannanda, Harisa Irma; WS, Hasanuddin; Hayati, Yenni (Universitas Negeri Padang, 2018)
The problem formulation in this research is how is hedonism in novel metropop Cewek Matre by Alberthiene Endah. The purpose of this study were (1) describes the form of behavior of hedonism in the novel metropop Cewek Matre by Alberthiene Endah; (2) to describe the cause of hedonism behavior in novel metropop Cewek Matre by Alberthiene Endah; and (3) describe the impact of hedonism behavior in novel metropop Cewek Matre by Alberthiene Endah. The data source of this research is novel metropop Cewek Matre by Alberthiene Endah. Data were collected by using descriptive method and triangulation technique as data validity. The research findings that form of hedonism behavior found as many as 40 data. The cause of hodonism behavior was found to be 46 data. The impact of hedonism behavior was found to be 67 data.Â Keywords: hedonism, metropop novel, literature